Alternative process for strawberry juice processing: Microwave hydrodiffusion and gravity. (October 2017) - Turk, Mohammad; Perino, Sandrine; Cendres, Aurélie; Petitcolas, Emmanuel; Soubrat, Thibault; Chemat, Farid
Abstract: The objective of this study was to evaluate the potential of Microwave Hydrodiffusion and Gravity as an alternative process for strawberry juice processing. The investigation entailed the optimization of extraction yields and energy consumption by varying the power density ( P s ) and the treatment vessel capacity ( C v ). The logistic function and Gompertz equation are used for the modeling of the extraction by microwaves. The models allow an acceptable prediction of MHG extraction performance. The optimal conditions were P s : 1000 W/kg and C v : 437.5 kg/m 3 which correspond in these conditions to 399.6 kJ/kg of energy consumption. At these optimal conditions, sugars, acids and the volatiles profile of MHG juice was compared with the profile of the fruit. The key markers of strawberry aroma are present in MHG juice, with a softer sensation than in fruit. Highlights: Microwave Hydrodiffusion (MHG) is suitable for strawberry juice extraction. Gompertz and logistic function are adequate for MHG modeling. Energy consumption is affected by specific power and vessel capacity. Key markers of strawberry aroma, sugars and organic acids are present in MHG juice.